2019
DOI: 10.1038/s41598-019-47983-y
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructuring with Structural-Compositional Dual Heterogeneities Enhances Strength-Ductility Synergy in Eutectic High Entropy Alloy

Abstract: A lamellar (L1 2 + B2) AlCoCrFeNi 2.1 eutectic high entropy alloy (EHEA) was severely deformed by a novel hybrid-rolling process. During hybrid-rolling, the deformation was carried out in two stages, namely cryo-rolling followed by warm-rolling at 600 °C. The strain (ε) imparted in each of these steps was identical ~1.2, resulting in a total strain of ε~2.4 (corresponding to 90% reduction in thickness). The novel processing strategy resulted in an extremely heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(10 citation statements)
references
References 44 publications
0
9
1
Order By: Relevance
“…Meanwhile, our CNL alloy shows a twofold strength and uniform elongation advantage over lamellar titanium alloys 35,36 . Even when compared with the recently reported lamellar high-entropy alloys (HEAs) 41,42 , our CNL alloy displays a simultaneous 50% increase in both yield strength and uniform ductility. Therefore, our CNL alloy exhibits an unprecedented combination of ultrahigh yield strength and large uniform ductility, which outperforms from other lamellar materials and high-performance nanostructured materials, thereby overcoming the long-standing dilemma of the strengthductility trade-off.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Meanwhile, our CNL alloy shows a twofold strength and uniform elongation advantage over lamellar titanium alloys 35,36 . Even when compared with the recently reported lamellar high-entropy alloys (HEAs) 41,42 , our CNL alloy displays a simultaneous 50% increase in both yield strength and uniform ductility. Therefore, our CNL alloy exhibits an unprecedented combination of ultrahigh yield strength and large uniform ductility, which outperforms from other lamellar materials and high-performance nanostructured materials, thereby overcoming the long-standing dilemma of the strengthductility trade-off.…”
Section: Discussioncontrasting
confidence: 63%
“…4 Tensile properties of our CNL alloy compared with those of other materials. The reference materials include lamellar-structured alloys (Ti alloy 35,36 , Fe alloy 37 , Co alloy 38 , Ni alloy 39 , Zr alloy 40 , HEA 41,42 , TiAl alloy 43 , pearlitic steel 44,45 , bainitic steel 46 , and twinning-induced plasticity (TWIP) steel 47 ), laminated metal composites (Al/Ti 48 , Ti/Ta 49 , Fe/Cu 50 , Cu/Zr 51 , Cu/Nb 52 , and steel/steel 53 ), and nanostructured metals (Al 54 , Ni 55 , Mo 56 , and W 57 ). Our CNL alloy (red dot) clearly outperforms other high-performance materials and overcomes the long-standing dilemma of the strength-ductility trade-off.…”
Section: Discussionmentioning
confidence: 99%
“…These alloys generally have fcc or L1 2 phase as a "soft" phase and B2, 𝜇, Laves, or other intermetallic phases as a "hard" reinforcement. In addition, thermomechanical processing was found to be a prospective method to enable a better strength-ductility combination in EHEAs [27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…Non-equimolar HEAs in the AlCrCoFeNi alloy family have also been investigated. Reddy et al (2019) found that severe deformation of AlCoCrFeNi 2.1 eutectic high entropy alloy by cryo-rolling and subsequent warm-rolling at 600 • C imparts high ductility and strength due to the unique lamellar structure (L1 2 +B2) that is formed.…”
Section: Introductionmentioning
confidence: 99%